Asymmetric cognitive, emotional and behavioural effects of values-related and performance-related negative brand publicity. Issue 2 (12th March 2018) - Liu, Xian; Lischka, Helena Maria; Kenning, Peter
Abstract : Purpose: This research aims to systematically explore the cognitive and emotional effects of values-related and performance-related negative brand publicity and investigate how the psychological effects translate into different behavioural outcomes. In addition, it examines the relative effectiveness of two major brand response strategies in mitigating negative publicity. Design/methodology/approach: Two experimental studies were conducted to test the hypotheses. Study 1 examines the effects of values- and performance-related negative brand publicity, using a 3 (negative brand publicity: values-related vs performance-related vs control) × 2 (brand: Dove vs Axe) between-subjects experiment. Study 2 further compares the effects of two major brand response strategies on consumers' post-crisis perceived trustworthiness and trust and responses towards a brand involved in negative publicity. A 2 (negative brand publicity: values-related vs performance-related) × 2 (brand response strategy: reduction-of-offensiveness vs corrective action) between-subjects design was used. Findings: The results suggest that values-related negative brand publicity is perceived as being more diagnostic and elicits a stronger emotion of contempt, but a weaker emotion of pity than performance-related negative brand publicity. Moreover, values-related negative brand publicity has a stronger negative impact on consumer responses than performance-related negative brand publicity. Interestingly, compared to perceived diagnosticity of information and the emotion of pity, the emotion of contempt is more likely to cause differences in consumer responses to these two types of negative brand publicity. Regarding brand response strategy, corrective action is more effective than reduction-of-offensiveness for both types of negative brand publicity, but the advantage of corrective action is greater for the performance-related case. Originality/value: This research enriches the negative publicity and brand perception literature, showing the asymmetric cognitive, emotional and behavioural effects of values- and performance-related negative brand publicity. It also identifies the psychological mechanisms underlying consumer responses to negative brand publicity, and it provides empirical evidence for the relative effectiveness of two major brand response strategies.